2002
DOI: 10.1002/sim.1203
|View full text |Cite
|
Sign up to set email alerts
|

Flexible parametric proportional‐hazards and proportional‐odds models for censored survival data, with application to prognostic modelling and estimation of treatment effects

Abstract: Modelling of censored survival data is almost always done by Cox proportional-hazards regression. However, use of parametric models for such data may have some advantages. For example, non-proportional hazards, a potential difficulty with Cox models, may sometimes be handled in a simple way, and visualization of the hazard function is much easier. Extensions of the Weibull and log-logistic models are proposed in which natural cubic splines are used to smooth the baseline log cumulative hazard and log cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
1,204
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,206 publications
(1,217 citation statements)
references
References 32 publications
(43 reference statements)
5
1,204
0
8
Order By: Relevance
“…For participants without a history of stroke, the time until stroke was observed until the end of the first extension period (2010). Adjusted hazard ratios were estimated through the Cox regression model framework accounting for left and right censoring that allowed a flexible spline fit to the baseline hazard 65. Models used age as the time scale and accounted for left censoring of participants who reported stroke before WHI enrollment and right censoring for those who did not have a stroke event.…”
Section: Methodsmentioning
confidence: 99%
“…For participants without a history of stroke, the time until stroke was observed until the end of the first extension period (2010). Adjusted hazard ratios were estimated through the Cox regression model framework accounting for left and right censoring that allowed a flexible spline fit to the baseline hazard 65. Models used age as the time scale and accounted for left censoring of participants who reported stroke before WHI enrollment and right censoring for those who did not have a stroke event.…”
Section: Methodsmentioning
confidence: 99%
“…The cubic spline models were based on those developed by Royston and Parmar. 192 Cubic spline models expressed on the proportional odds scale were used as they appeared to converge to an optimised solution more frequently than the proportional hazards or probit variants of the cubic spline model. A series of one-, two-, three-and four-knot spline models was considered.…”
Section: Input Assumptionmentioning
confidence: 99%
“…However, it has recently been suggested that RSRs should be estimated using a modelling approach that enables flexible modelling of the baseline excess hazard [7], and one such model is the flexible parametric survival model [22,23].…”
Section: Relative Survivalmentioning
confidence: 99%
“…The flexible parametric survival model [22,23] uses restricted cubic splines to model the baseline cumulative hazard. The use of splines enables the model to capture complex baseline cumulative hazard functions, and gives a parametric model without the need of strong distributional assumptions.…”
Section: Flexible Parametric Survival Modelmentioning
confidence: 99%